Price discovery in the cryptocurrency option market: A univariate GARCH approach - Pierre J. Venter; Eben Maré; Edson Pindza (Cogent Economics & Finance, 2020)
In this paper, two univariate generalised autoregressive conditional heteroskedasticity (GARCH) option pricing models are applied to Bitcoin and the Cryptocurrency Index (CRIX). The first model is symmetric and the other takes asymmetric effects into account. Furthermore, the accuracy of the GARCH option pricing model applied to Bitcoin is tested. Empirical results indicate that asymmetry is not an important factor to consider when pricing options on Bitcoin or CRIX, this is consistent with findings in the literature. In addition, the GARCH option pricing model provides realistic price discovery within the bid-ask spreads suggested by the market.
Keywords: 330; CRIX; cryptocurrencies; GARCH; option pricing; volatility surface